Total sugars in atmospheric aerosols: an alternative tracer for biomass burning - Scaramboni, Caroline; Urban, Roberta Cerasi; Lima-Souza, Michele [UNESP]; Nogueira, Raquel Fernandes Pupo [UNESP]; Cardoso, Arnaldo Alves [UNESP]; Allen, Andrew George [UNESP]; Campos, Maria Lúcia Arruda de Moura (Elsevier B.V., 2015)
Ambient aerosols were collected in an agro-industrial region of Sao Paulo State (Brazil) between May 2010 and February 2012 (n = 87). The atmosphere of the study region is highly affected by the emissions of gases and particles from sugar and fuel ethanol production, because part of the area planted with sugarcane is still burned before manual harvesting. This work proposes the quantification of total sugars as an alternative chemical tracer of biomass burning, instead of levoglucosan. The quantification of total sugars requires a small area of a filter sample and a simple spectrophotometer, in contrast to the determination of levoglucosan, which is much more complex and time-consuming. Total sugars concentrations in the aerosol ranged from 0.28 to 12.5 mu g m(-3), and (similarly to levoglucosan) the emissions were significantly higher at night and during the sugarcane harvest period, when most agricultural fires occur. The linear correlation between levoglucosan and total sugars (r = 0.612) was stronger than between levoglucosan and potassium (r = 0379), which has previously been used as a biomass burning tracer. In the study region, potassium is used in fertilizers, and this, together with substantial soil dust resuspension, makes potassium unsuitable for use as a tracer. On average, ca. 40% of the total sugars was found in particles smaller than 0.49 mu m. By including data from previous work, it was possible to identify from 35 to 42% of the total sugars, with biomass burning making the largest contribution. The high solubility in water of these sugars means that determination of their concentrations could also provide important information concerning the hydrophilic properties of atmospheric aerosols.
Keywords: Biomass burning marker; Sugarcane; Ethanol production; Brazil; Aerosol